Malik Bennabi's Ideas on Civilization and the Development of the Society : Perspectives on Education - Aomar, Nakib (2004)
The study is concerned with Malik Bennabi's ideas on civilization and the development of society in the Muslim world, with the focus on education. The purpose is to reveal the nature of his ideas and views on education in order to conceptualize them in the form of an integrated approach to the educational problem in the Muslim world. Due to the nature of the research problem, qualitative methodology was employed in this study. This study involved an investigation into Malik Bemabi's thoughts from three sources of evidence; Malik Bennabi's works, the different studies carried out on his thoughts and interviews. The content analysis and interviews were employed to examine the data in addressing the research questions. Content analysis; as a technique, dealt with documentary evidence. The interviews provided additional information gathered fiom personalities acquainted with Malik Bennabi's thoughts. The findings of this study show that Malik Bennabi made a considerable contribution to the enrichment of the Islamic educational thought by suggesting a range of rich and enduring ideas that may contribute to the solution of the Muslim dilemma. Four parameters are crucial to grasp the nature of Malik Bennabi's approach to the educational problem in the Muslim world; religion as a cosmic phenomenon, Islam as the principal fkame of reference, the Islamic problem as civilizational in nature and the human factor as the major factor of the Muslim world's civilizational problems. The methodological approach to study the problems of civilization adopted by Malik Bennabi had an explicit impact on defining the concept of education. Man, the Muslim, is the central factor in the study of the problems of civilization in the Muslim world. Education is the process of civilizing the human being and imparting to his existence a historical significance in order to enable him to resume his historical mission. Many concepts have been treated in Malik Bennabi's works. However, due to their educational nature, the concepts form together the essential elements upon which the process of education is established. Malik Bennabi treated four philosophical foundations of education; the nature of man, society, knowledge and the aims of education. Malik Bennabi provided Islamic education with a new approach to conceptualize the educational problem and education as a project to promote a new culture and build up a civilization. This approach considers the Islamic problem as civiIizationa1 in nature but an educational matter. Malik Bennabi did not present his ideas and views on education in a systematic manner. However, these ideas may form together an integrated approach to conceptualize the educational problem in the Muslim world as a problem of civilization. So, it is recommended that future studies should attempt to formulate this approach integrally based on the findigs of this study.